Annotazioni sul «Buef d’Aigremont» (prologo del «Renaut de Montauban») nel ms. Venezia, Biblioteca Nazionale Marciana, fr. Z. 16 (= 229) (Carte Romanze, 2024)
Abstract: The manuscript V16 (Venezia, Biblioteca Nazionale Marciana, fr. Z 16) contains a Franco-Italian version of Renaut de Montauban that Ferdinand Castets, Karl Triebel, Karl Kaiser, Ernst Geipel, and Jacques Thomas have considered innovative compared to the other twelve versions in verse, particularly regarding the prologue called Buef d’Aigremont. To verify this claimed innovation, the versions of ms. L edited by Castets (1909) and ms. D published by Thomas (1989) are systematically compared with the text of V16. From this analysis, which intersects both the synopsis of the laisses and the contents, there would be a significant reassessment of the originality of V16. However, this reevaluation does not affect the hope of Günter Holtus and Peter Wunderli that the only version of Renaut de Montauban produced in Italy might finally see the light in a critical edition. Keywords: Renaut de Montauban, Franco-Italian epics, prologue, macrovariance.